Belonging, Citizenship and Ambivalence among Young Gay, Bisexual and Queer Indian Singaporean Men. Issue 1 (2nd January 2021) - Prankumar, Sujith Kumar; Aggleton, Peter; Bryant, Joanne
ABSTRACT: This article explores the attitudes and experiences of young ethnic Indian gay, bisexual and queer (GBQ) men in Singapore, where the state's investments in economic progress, racial governmentality and "traditional" family policies significantly influence sexual and cultural citizenship. Based on abductively analysed in-depth interviews conducted on a subset of a larger qualitative study involving Singaporean lesbian, gay, bisexual and queer young adults, this article uses the concept of sociological ambivalence – which attends to the tensions between social structures and participants' lives – to understand everyday experiences at the intersections of ethnicity, sexuality, gender and youth status. Three themes were identified from participants' experiences: significant feelings of racialised liminality and marginality; tensions between personal desires and family pressures to get married and have children; and strategies taken in response to complex marginality. While participants were broadly satisfied with the material aspects of life in Singapore, their responses signal significant frustration with societal and sexual racism, a deeply ambivalent sense of belonging, and the desire for emigration to mitigate conflicting responsibilities to themselves and their families. By examining belonging and citizenship through the lens of sociological ambivalence, this article makes a theoretical and empirical contribution towards limited knowledge about the experiences of marginalised populations in Singapore.